Development of magnetically recyclable visible light photocatalysts for hydrogen peroxide production. (15th June 2020) - Pal, Shaili; Kumar, Sunil; Verma, Alkadevi; Kumar, Ajay; Ludwig, Tim; Frank, Michael; Mathur, Sanjay; Prakash, Rajiv; Sinha, Indrajit
Abstract: The development of magnetically recyclable photocatalysts for economic and green H2 O2 synthesis from water and oxygen only is virtually unexplored. Magnetic recyclability makes possible cost-effective laboratory or industrial reuse of the catalyst. The present research shows that magnetically recyclable starch functionalized Fe3 O4 /Ag/Ag2 O superparamagnetic nanocomposites are very good visible light photocatalysts for H2 O2 formation. These nanocomposites were prepared by precipitating Ag/Ag2 O fine-sized nanostructures on starch functionalized magnetite nanoparticles (SMNPs). HR-TEM, XRD, and XPS analysis results showed the formation of SMNPs dotted with fine-sized Ag/Ag2 O nanostructures smaller than their quantum confinement regimes. A p-n heterojunction is formed between (n-type) starch functionalized magnetite and (p-type) Ag2 O components. Enhanced charge separation and the presence of plasmonic Ag nanostructures on the SM component cause efficient oxygen reduction with high H2 O2 formation rates. Highlights: Green synthesis of starch functionalized Fe3 O4 /Ag/Ag2 O nanocomposites. Economic and green H2 O2 synthesis from water and oxygen only. Magnetically recyclable p-n heterojunction visible light photocatalysts. Millimolar level photocatalytic production of H2 O2 .